Надежность многозначных структур - Григорьев В. В. Валерий Владимирович; Кметь А. Б. Аркадий Борисович; Коноплянко З. Д. Зеновий Дмитриевич; Раков М. А. Михаил Аркадьевич; Смоляк А. М. Александр Михайлович; Шеремет Е. М. Ефим Михайлович (Киев, Наук. думка, 1981)
Авт. указаны на обороте тит. л.